Strategic Plan Design for Business Formulation and Simple Financial Report Bookkeeping Training - Ayu Ambang Lestari; Arie Cahyani; Wiwik Wida Farwati; Ni Putu Karinina Febriyanty (Communautaire: Journal of Community Service, 2025)
This study aims to analyze and identify solutions to the managerial and financial problems faced by micro-enterprises in the barbershop sector. The study is based on a lack of understanding of business planning and basic financial record-keeping, which hinders business growth and competitiveness. The method used is a participatory and applied approach, involving barbershop owners and employees at every stage of the activity. The first stage is needs identification through surveys and interviews, followed by business strategy socialization and simple financial bookkeeping training. Evaluation was conducted using pre- and post-tests to measure the increase in participants' knowledge. The results showed a significant increase in understanding of business planning, operational management, and financial bookkeeping after the training. The recommendations from this study are the need for a longer implementation period, ongoing mentoring, and the involvement of relevant parties such as local governments or financial institutions to increase the sustainability of the program. This study contributes to proving that participatory and practice-based empowerment programs can improve the managerial and financial capacity of micro-enterprises, thereby supporting the growth and competitiveness of small businesses like Matahari Barbershop.